Eхperience of endoscopic decompression of the suprascapular nerve - Evgeniy A. Belyak; Dmitry L. Pashin; Fedor L. Lazko; Alexey P. Prizov; Maxim F. Lazko; Nikolay V. Zagorodniy; Sarkis A. Asratyan (Клиническая практика, 2022)
Background: Suprascapular nerve neuropathy is a commonly spread pathology, caused by a traction force trauma or compression in the scapular notch area. In the case of a conservative treatment failure, a standard surgical procedure is neurolysis (decompression) of the suprascapular nerve in the scapular notch. This procedure can be done in an open manner or endoscopically. Aims: to evaluate the results of endoscopic decompression of the suprascapular nerve in the scapular notch area at a 6 months follow-up. Methods: We operated 10 patients with the clinical picture of posttraumatic suprascapular nerve neuropathy in the period from 2015 to 2021. The mean age of patients was 52.311.8. All the patients underwent the shoulder joint and subacromial space arthroscopy, and decompression of the suprascapular nerve in the scapular notch area. Results: According to the VAS-scale, the severity of pain syndrome before the surgery was 6 cm, while in 6 months after the surgery it decreased to 2 cm. According to the DASH scale, the dysfunction of the of shoulder joint before the surgery was 70 points, in 6 months after the surgery it decreased to 10 points. The range of motion in the shoulder joint before the surgery was: flexion 15514,4, abduction 14042, external rotation 125,6; 6 months after the surgery we observed: flexion 17415,6, abduction 17514,4, external rotation 489. Conclusion: The obtained results let us characterize the method of endoscopic decompression of the suprascapular nerve as a low-traumatic and effective technique, which promotes restoration of the function of the suprascapular nerve and shoulder joint, and elimination of pain syndrome from the shoulder area.